Characterization of Aquifer System and Groundwater Storage Change Due to South-to-North Water Diversion Project at Huairou Groundwater Reserve Site, Beijing, China, Using Geodetic and Hydrological Data - Mingjia Li; Jianbao Sun; Lian Xue; Zhengkang Shen; Bin Zhao; Leyin Hu (Remote Sensing, 2022)
Groundwater overexploitation is a critical issue in the North China Plain (NCP), resulting in groundwater level decline and surface subsidence for the last half-century. This problem, however, has been greatly alleviated by the South-to-North Water Diversion (SNWD) Project since 2015. Monitoring of this process has been steadily improved in recent years using water level and geodetic observations. Here, we characterize the water storage change at the Huairou groundwater reserve site (HGRS) in Beijing due to the SNWD by combining Interferometric Synthetic Aperture Radar (InSAR) data of the Sentinel-1 satellites, continuous Global Positioning System (GPS) data, and well water level data observed during the same time. InSAR observations revealed subsidence up to ~400 mm in the Beijing plain but uplift at ~40 mm in the HGRS during 2015–2019, and more than 70% of the uplift occurred from October 2018 to January 2019. By integrating the most significant uplift deformation during October 2018 to January 2019 with water level observations at the same time, we estimated the storativity of the confined aquifer system at HGRS as <semantics>1.68–7.82×10−3</semantics>, weighing in the correction for effective stress and surface deformation for various situations. Based on the estimated aquifer storativity and the observed water level change in the unconfined and confined aquifer, the recharged water storage for the confined and unconfined aquifers was estimated as <semantics>1.20–1.39×107 m3</semantics> and ~<semantics>2.86×108 m3</semantics> from 6 October 2018 to 22 January 2019, respectively, which is about 4% and 91% of the surface water recharge through river channels in the same period due to the SNWD Project. Our study demonstrates that integration of geodetic and hydrological data can provide crucial information for the assessment of groundwater circulation and assistance of groundwater management.